Evaluation of Hexane Content in Edible Vegetable Oils Consumed in Iran - Mojtaba, Yousefi; Hedayat, Hosseini (Journal of Experimental and Clinical Toxicology, 2017)
Solvent residue such as hexane in foodstuff, especially edible oil could be considered as the undesirable substances when exceeds maximum residue limit (MRL). The aim of this study is to determine the hexane content in various brands of edible oils. Totally forty samples (23 brands) of different types of vegetable oils including frying oils (n=14), blended oils (n=13), sunflower oils (n=6), corn oils (n=5) and canola oils (n=2) from Iran´s market were analyzed for hexane content using solid phase microextraction gas chromatography equipped with a flame-ionization detector (SPME)-GC-(FID). The hexane residue was detected in thirty-six out of forty examined samples, ranged from lower than LOD to 42.6 µg/kg. However, in all of them hexane content were below the MRL of 1 mg/kg which set by the European Union.
Keywords: Edible oils; Hexane; GG; Solvent residue